Prevalence of sexual coercion and associated factors among adolescents and young adults in Africa: a systematic review and meta-analysis - Aduroja, Posi Emmanuel; Afolabi, Adebukunola Olajumoke; Bakare, Ayobami Adebayo; Olabisi, Oluwaseyi Isaiah; Atinga, Atimi; Bashiru, Hameed Akande; Solomon, Abiola; Adufe, Iyanu; Oghide, Oziegbe; Okeke, Oluchukwu Perpetual; Abodunrin, Olunike Rebecca; Akinsolu, Folahanmi; et al. (Frontiers in Reproductive Health, 2025)
IntroductionSexual coercion is a major public health and human rights concern, yet its burden among African adolescents and young adults remains poorly synthesized. This review aimed to estimate the prevalence of sexual coercion in this population and examine variations by gender, setting, and region.MethodsWe systematically searched Web of Science, Scopus, MEDLINE/PubMed, and CINAHL for studies published between January 2000 and June 2025. Two reviewers independently screened, extracted, and appraised eligible studies. A narrative synthesis was integrated with a random-effects meta-analysis due to anticipated high heterogeneity to derive pooled prevalence estimates and conduct subgroup analyses.ResultsThirty-three studies involving 63,934 participants from 14 African countries were included. The pooled prevalence of sexual coercion was 20% (95% CI: 17%–23%). Females reported higher prevalence (23%) than males (19%). School-based studies showed greater prevalence (26%) compared with community-based studies (16%).DiscussionSexual coercion remains a major public health and human rights concern among African adolescents, particularly school-going females. Strengthening school- and community-based programs that integrate comprehensive sexuality education on consent, negotiation, and gender equality is essential. Developing a standardized, context-sensitive tool for measuring sexual coercion will also enhance evidence quality and policy response.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251067378, PROSPERO CRD420251067378.